The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1155/2021/2510847
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Multiomics Analysis Identifies a Novel Biomarker Associated with Prognosis in Intracerebral Hemorrhage

Abstract: Existing treatments for intracerebral hemorrhage (ICH) are unable to satisfactorily prevent development of secondary brain injury after ICH and multiple pathological mechanisms are involved in the development of the injury. In this study, we aimed to identify novel genes and proteins and integrated their molecular alternations to reveal key network modules involved in ICH pathology. A total of 30 C57BL/6 male mice were used for this study. The collagenase model of ICH was employed, 3 days after ICH animals wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 57 publications
(59 reference statements)
0
7
0
Order By: Relevance
“…44,45,88 However, increasing data have challenged this concept. Clinically, SERPINA3 was reported to be elevated in the body fluid (plasma and CSF) of individuals affected by AD, 5 MS, 7 stroke, 89 intracerebral haemorrhage (ICH), 62 brain tumours 90 and normal ageing 73 funding procurement, Fuzheng Guo, Yan Wang.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…44,45,88 However, increasing data have challenged this concept. Clinically, SERPINA3 was reported to be elevated in the body fluid (plasma and CSF) of individuals affected by AD, 5 MS, 7 stroke, 89 intracerebral haemorrhage (ICH), 62 brain tumours 90 and normal ageing 73 funding procurement, Fuzheng Guo, Yan Wang.…”
Section: Discussionmentioning
confidence: 99%
“…However, increasing data have challenged this concept. Clinically, SERPINA3 was reported to be elevated in the body fluid (plasma and CSF) of individuals affected by AD, 5 MS, 7 stroke, 89 intracerebral haemorrhage (ICH), 62 brain tumours 90 and normal ageing 73 and positively correlated with respective disease burden/progression or poor outcomes. These clinical observations suggest that Serpina3n/SERPINA3 represents a common mechanism and a therapeutic target for shared disease pathophysiology.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that C1QB and C1QC play an important role in the pathogenesis of atherosclerosis [34,39]. ITGB2 (CD18), a cell-surface glycoprotein, belongs to the integrin family and acts as a coordinator of extra-and intracellular signaling [40]. Traditionally considered important regulators of cell survival, proliferation, adhesion, and migration [41], De cient ITGB2 could also exert a neuroprotective effect by reducing in ltrating leukocytes, which decrease in ammatory cytokines and chemokines [42].…”
Section: Discussionmentioning
confidence: 99%
“… 11 Conversely, recent studies have found that SERPINA3 might be a potential biomarker of poor functional outcome in patients with ICH. 12 This dual nature of SERPINA3, potentially acting as both a protective agent in ischemic stroke and a risk factor in ICH, underlines the complexity of cerebrovascular system and the diverse roles that a single protein can play within it. In our current investigation, we observed a potential link between SERPINA3 and CSVD, where higher level of SERPINA3 was associated with greater severity of WMH, a prominent imaging hallmark of CSVD.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we selected several candidate inflammatory molecules that could potentially be associated with CSVD. Serine proteinase inhibitor A3 (SERPINA3), a member of the serine protease inhibitor superfamily, has been reported to participate in pathological inflammatory processes of numerous neurological diseases such as ischemic stroke, 11 intracerebral hemorrhage, 12 and Alzheimer's disease. 13 However, despite being a potential predisposing factor for ischemic stroke, the relationship between CSVD burden and SERPINA3 has never been investigated in patients with IS.…”
Section: Introductionmentioning
confidence: 99%